How Dimerization Through a Spiro Junction Modifies the Nonlinear Optical Properties of a Push–Pull Organic Dye: Insights from Theory and Hyper‐Rayleigh Scattering. Issue 3 (19th January 2017) - Castet, Frédéric; Lerychard, Timothée; Pielak, Kornelia; Szalóki, György; Dalinot, Clément; Leriche, Philippe; Sanguinet, Lionel; Champagne, Benoît; Rodriguez, Vincent
Abstract: The second‐order nonlinear optical (NLO) properties of a push–pull monomer, as well as of its dimer composed of two monomeric units connected through a non‐conjugated spiro junction, are investigated by means of hyper‐Rayleigh scattering (HRS) and quantum chemical calculations. It is shown that dimerization to form a molecule with an orthogonal geometry enhances the first hyperpolarizability by circa 20 % and induces a decrease of the dipolar character of the HRS response. Theoretical calculations correlate well with experimental measurements and allow an in‐depth rationalization of the impact of the spiro linkage on the NLO properties through a detailed analysis of the relevant electronic excited states. Abstract : Give and take : Dimerization of a push–pull chromophore through an orthogonal spiro junction enhances the first hyperpolarizability by circa 20 %, as demonstrated by means of hyper‐Raleigh scattering and quantum chemical calculations. Dimerization is found to slightly decrease the dipolar character of the nonlinear optical response.